If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 120 = y Reorder the terms: 120 + -2x = y Solving 120 + -2x = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-120' to each side of the equation. 120 + -120 + -2x = -120 + y Combine like terms: 120 + -120 = 0 0 + -2x = -120 + y -2x = -120 + y Divide each side by '-2'. x = 60 + -0.5y Simplifying x = 60 + -0.5y
| 2y-16=4x | | 8y-2y+16=40 | | 74=x^3 | | y=-2(x-6) | | (7x-2)37=437 | | 73=x^3 | | 12+5=k+49 | | 88-16b=-16b+88 | | 78=-9-3(-56+12x) | | -x^2+10x+22=0 | | 7x-12=-36-11 | | logx=3.45 | | (y+2)/2-(2y-6)/3=1 | | 47-4m=7-12m | | 38.2x+41.7-12.9x-43.3= | | 77=4-10y+3 | | 8+x=14-2x | | -60x^2+5=0 | | -7w-3w+4w=-15 | | -19+7=12 | | -12(a-12)=-50 | | 8g+20=76 | | 8+x=12-2x | | 7(1+7m)=7+6m | | 21-3(2-a)=-12 | | 8+x=13-2x | | 15x-30(x+4)=9(x-25) | | 1.9+6p=7.69 | | -7(1+4N)-3N=-224 | | 3n+4=5n-20 | | 6(3-4.5x)=8.5-9x | | .666x=6 |